2015
DOI: 10.3390/ijerph121114669
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure in Healthy Korean Weaning-Age Infants: Association with Growth, Feeding and Fish Intake

Abstract: Low-level mercury (Hg) exposure in infancy might be harmful to the physical growth as well as neurodevelopment of children. The aim of this study was to investigate postnatal Hg exposure and its relationship with anthropometry and dietary factors in late infancy. We recruited 252 healthy Korean infants between six and 24 months of age from an outpatient clinic during the 2009/2010 and 2013/2014 seasons. We measured the weight and height of the infants and collected dietary information using questionnaires. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…The implications of family Hg exposure resulting from fish consumption on young children’s anthropometric indices can be contradictory. While some authors reported negative [ 34 ] and positive [ 35 ] influence of Hg on childhood anthropometric indices, others have not inferred such a relationship in their reports [ 15 , 36 , 37 ]. Still, others have indicated that Hg has no influence on Z-scores of height and weight indices in children ≤6-years-old; however, an increase in Hg concentrations was associated with a higher body mass index (BMI) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implications of family Hg exposure resulting from fish consumption on young children’s anthropometric indices can be contradictory. While some authors reported negative [ 34 ] and positive [ 35 ] influence of Hg on childhood anthropometric indices, others have not inferred such a relationship in their reports [ 15 , 36 , 37 ]. Still, others have indicated that Hg has no influence on Z-scores of height and weight indices in children ≤6-years-old; however, an increase in Hg concentrations was associated with a higher body mass index (BMI) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylmercury can pass through the blood-brain barrier and placenta, potentially affecting the brain and/or fetus. Therefore, additional care is required for children and pregnant women to minimize exposure [24][25][26] . The present study reported the case of a 48-year-old deep-sea fisherman who presented to the hospital with paresthesia and pain in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The As, Cd, Hg, and Pb levels in the same venous whole blood samples of the infants were determined using Inductively-Coupled Plasma Mass Spectrometry (Agilent 7700, Santa Clara, CA, USA) at the Green Cross Reference Laboratory (Yongin-City, Kyunggi-do, Korea) as previously described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Exclusively/mostly breastfeeding and mostly formula feeding were defined as previously described [25]. The infants who were not classified as mostly breastfed or mostly formula fed were defined as have mixed feeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation